Unraveling Tax Compliance: Imperatives for Online Businesses in the Global Landscape - Kharis, Dwishar; Rosnawati, Emy (Proceedings of The ICECRS, 2023)
This study delves into the intricate realm of online businesses' tax behavior, elucidating their compliance with diverse tax laws and regulations across borders. Focusing on accurate income and expense reporting, timely tax return filing, and punctual tax payments, our research illuminates the critical importance of good tax behavior in the digital business landscape. Through a comprehensive analysis of legal frameworks, our findings underscore the substantial penalties and fines, including potential criminal charges, faced by non-compliant businesses. Furthermore, we explore the nuanced challenges posed by international tax laws, especially for businesses operating across multiple countries. The implications of this study emphasize the necessity for online businesses to engage qualified tax professionals, ensuring meticulous adherence to all relevant tax regulations.Highlights : Critical Compliance: Examines online businesses' adherence to diverse tax laws globally, emphasizing accurate reporting and punctual payments, highlighting the necessity for meticulous tax compliance. Legal Challenges: Explores the complexities of international tax laws faced by businesses operating across borders, illuminating the legal intricacies and potential penalties for non-compliance. Professional Guidance: Emphasizes the vital role of qualified tax professionals, underscoring their significance in ensuring online businesses' meticulous adherence to relevant tax regulations, mitigating legal risks. Keywords: Tax compliance, Online businesses, Cross-border regulations, Legal frameworks, International taxation.